Structure of and influence of a tick complement inhibitor on human complement component 5 (vol 9, pg 753, 2008) - Fredslund, F; Laursen, N; Roversi, P; Jenner, L; Oliveira, C; Pedersen, J; Nunn, M; Lea, S; Discipio, R; Sottrup-Jensen, L; Andersen, G (2008)
To provide insight into the structural and functional properties of human complement component 5 (C5), we determined its crystal structure at a resolution of 3.1 Å. The core of C5 adopted a structure resembling that of C3, with the domain arrangement at the position corresponding to the C3 thioester being very well conserved. However, in contrast to C3, the convertase cleavage site in C5 was ordered and the C345C domain flexibly attached to the core of C5. Binding of the tick C5 inhibitor OmCI to C5 resulted in stabilization of the global conformation of C5 but did not block the convertase cleavage site. The structure of C5 may render possible a structure-based approach for the design of new selective complement inhibitors.